Gesture alignment in teacher–student interaction: a study concerning office hour consultations using English as the lingua franca - Opazo, Paloma; Cienki, Alan; Oben, Bert; Brône, Geert (Frontiers in Communication, 2024)
IntroductionIn this study, we explore the presence of gesture alignment in office hour consultations, a form of academic talk characterized by private face-to-face dialogues between a lecturer and a university student. Unlike classroom interactions, the topic of these consultations is initiated by the student. Our objectives were to describe the patterns of gesture alignment in these educational settings, to determine the direction of the copied behavior (i.e., who copies whom?), and to understand the temporal structuring of these instances.MethodsWe analyzed 12 office hour consultations, involving Spanish undergraduate students and lecturers from universities in England, Ireland, and Sweden. All the conversations were held in English. The annotation considered three domains: the timing of matching gestures (i.e., if the aligned gestures appeared in a Simultaneous, Consecutive, or Later manner), the form features of the aligned gestures (hand shape, movement, and orientation), and the function of the gestures (representational, deictic, or pragmatic).ResultsOur results show that although there are important differences between dyads, there were four general findings. First, aligned gestures mostly took place in a Consecutive manner. Second, gesture alignment is shown to achieve shared understanding between interactants, but this can be manifested in different ways: from the active negotiation of meaning to the signaling of agreement. Third, paired gestures become useful in educational contexts where the teachers and students include native and non-native speakers, as they contribute to disambiguating meaning. Fourth, many cases of matching gestures happen due to the presence of recurrent gestural forms.DiscussionOverall, our results are in line with previous evidence that has highlighted the role of gesture alignment in grounding processes, related to the achievement of mutual agreement between participants. Matching gestures are a helpful resource during office hour consultations—a form of academic talk where content is being explained and negotiated.